Basal ganglia network by constrained spherical deconvolution: A possible cortico‐pallidal pathway?. Issue 3 (22nd August 2014) - Milardi, Demetrio; Gaeta, Michele; Marino, Silvia; Arrigo, Alessandro; Vaccarino, Gianluigi; Mormina, Enricomaria; Rizzo, Giuseppina; Milazzo, Carmelo; Finocchio, Giovanni; Baglieri, Annalisa; Anastasi, Giuseppe; Quartarone, Angelo
Abstract In the recent past, basal ganglia circuitry was simplified as represented by the direct and indirect pathways and by hyperdirect pathways. Based on data from animal studies, we hypothesized a fourth pathway, the cortico‐pallidal, pathway, that complements the hyperdirect pathway to the subthalamus. Ten normal brains were analyzed by using the high angular resolution diffusion imaging—constrained spherical deconvolution (CSD)‐based technique. The study was performed with a 3T magnetic resonance imaging (MRI) scanner (Achieva, Philips Healthcare, Best, Netherlands); by using a 32‐channel SENSE head coil. We showed that CSD is a powerful technique that allows a fine evaluation of both the long and small tracts between cortex and basal ganglia, including direct, indirect, and hyperdirect pathways. In addition, a pathway directly connecting the cortex to the globus pallidus was seen. Our results confirm that the CSD tractography is a valuable technique allowing a reliable reconstruction of small‐ and long‐fiber pathways in brain regions with multiple fiber orientations, such as basal ganglia. This could open a future scenario in which CSD could be used to focally target with deep brain stimulation (DBS) the small bundles within the basal ganglia loops. © 2014 International Parkinson and Movement Disorder Society